The Reflection of Moral Ethics in Public Policy: An Analysis of Abdurrahman Wahid’s Thought on the Asta Cita Pillars - Kristiyadi, Diki; Miftahuddin, Miftahuddin (POLITEA, 2025)
The National Medium-Term Development Plan (RPJMN) 2025–2029, as stipulated in Presidential Regulation of the Republic of Indonesia No. 12 of 2025, includes the Asta Cita as the eight priority agendas for national development. These priorities include strengthening the Pancasila ideology, improving human quality, bureaucratic reform, and enforcing the law and human rights. This article examines the relevance of Abdurrahman Wahid's (Gus Dur) ideas in the implementation of the Asta Cita policy using a public policy theory framework that emphasises normative and practical dimensions. Gus Dur's thoughts, as outlined in his works Islamku, Islam Anda, Islam Kita (2006) and Prisma Pemikiran Gus Dur (Maarif Institute, 2021), emphasise the importance of inclusivity, tolerance, social justice, and respect for human rights as the foundation for civilised development. This study shows that the integration of Gus Dur's moral values into the Asta Cita policy can strengthen the legitimacy and effectiveness of national policies in Indonesia. Thus, Gus Dur's thoughts become a strategic foundation to ensure that national development is not only based on technocratic aspects but also on human values that uphold pluralism and democracy.